Staphylococcus aureus infections in Australasian neonatal nurseries. Issue 4 (21st June 2004) - Isaacs, D; Fraser, S; Hogg, G; Li, H Y
Abstract : Objective: To study the incidence and outcome of systemic infections with methicillin sensitive (MSSA) and methicillin resistant Staphylococcus aureus (MRSA) infections in Australasian neonatal nurseries. Methods: Prospective longitudinal study of systemic infections (clinical sepsis plus positive cultures of blood and/or cerebrospinal fluid) in 17 Australasian neonatal nurseries. Results: The incidence of early onset sepsis with S aureus, mainly MSSA, was 19 cases per 244 718 live births or 0.08 per 1000. From 1992 to 1994, MRSA infections caused only 8% of staphylococcal infections. From 1995 to 1998, there was an outbreak of MRSA infection, in two Melbourne hospitals. The outbreak resolved, after the use of topical mupirocin and improved handwashing. Babies with MRSA sepsis were significantly smaller than babies with MSSA sepsis (mean birth weight 1093 v 1617 g) and more preterm (mean gestation 27.5 v 30.3 weeks). The mortality of MRSA sepsis was 24.6% compared with 9.9% for MSSA infections. The mortality of early onset MSSA sepsis, however, was 39% (seven of 18) compared with 7.3% of late onset MSSA infection presenting more than two days after birth. Conclusions: S aureus is a rare but important cause of early onset sepsis. Late onset MRSA infections carried a higher mortality than late onset MSSA infections, but babies with early onset MSSA sepsis had a particularly high mortality.